Time trends in leisure time physical activity and physical fitness in elderly people: 20 year follow-up of the Spanish population national health survey (1987-2006) - Carrasco-Garrido Pilar; Hernández-Barrera Valentin; Jiménez-Garcia Rodrigo; Alonso-Blanco Cristina; Palacios-Ceña Domingo; Pileño-Martinez Elena; Fernández- (BMC, 2011)
Abstract Background To estimate trends in leisure time physical activity and physical fitness between 1987-2006 in older Spanish people. Methods We analyzed data collected from the Spanish National Health Surveys conducted in 1987 (n = 29,647), 1993 (n = 20,707), 1995-1997 (n = 12,800), 2001 (n = 21,058), 2003 (n = 21,650), and 2006 (n = 29,478). The number of subjects aged ≥ 65 years included in the current study was 29,263 (1987: n = 4,958-16.7%; 1993: n = 3,751-17.8%; 1995-97: n = 2,229-17.4%; 2001: n = 4,356-20.7%; 2003: 6,134-28.3%; 2006: 7,835-26.5%). Main variables included leisure-time physical activity and physical fitness. We analyzed socio-demographic characteristics, self-rated health status, lifestyle habit and co-morbid conditions using multivariate logistic regression models. Results Women exhibited lower prevalence of leisure time physical activity and physical fitness compared to men (P < 0.05). The multivariate analysis for time trends found that practising leisure time physical activity increased from 1987 to 2006 (P < 0.001). Variables associated with a lower likelihood of practicing leisure time physical activity were: age ≥ 80 years old, ≥ 2 co-morbid chronic conditions, and obesity. Variables associated with lower physical fitness included: age ≥ 80 years, worse self rated health; ≥ 2 medications (only for walking), and obesity. Conclusions We found an increase in leisure time physical activity in the older Spanish population. Older age, married status, co-morbid conditions, obesity, and worse self-perceived health status were associated with lower activity. Identification of these factors can help to identify individuals at risk for physical inactivity.